THE EFFECT OF COMPANY SIZE, PROFITABILITY, LIQUIDITY, AND LEVERAGE ON COMPANY VALUE IN THE INFRASTRUCTURE SECTOR 2020-2024: PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, LIKUIDITAS, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PADA SEKTOR INFRASTRUKTUR 2020-2024 - Nelin Elisa, Nelin Elisa (Program Studi Akuntansi Universitas Islam Lamongan, 2026)
This study aims to analyze the effect of firm size, profitability, liquidity, and leverage on firm value in infrastructure sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Firm value is proxied by Price to Book Value (PBV), firm size by the natural logarithm of total assets (Ln Total Assets), profitability by Return on Assets (ROA), liquidity by Current Ratio (CR), and leverage by Debt to Equity Ratio (DER). This research applies a quantitative approach using multiple linear regression analysis with purposive sampling technique, resulting in 54 observations. The data used are secondary data obtained from companies’ annual financial statements. The results indicate that partially firm size, profitability, liquidity, and leverage have a significant effect on firm value, and simultaneously all independent variables significantly influence firm value. The coefficient of determination shows that 48.5% of the variation in firm value can be explained by the variables in this research model, while the remaining percentage is influenced by other factors outside the study.